2011
DOI: 10.1007/s11207-011-9788-4
|View full text |Cite
|
Sign up to set email alerts
|

Radio Emission of the Quiet Sun and Active Regions (Invited Review)

Abstract: Solar radio emission provides valuable information on the structure and dynamics of the solar atmosphere above the temperature minimum. We review the background and most recent observational and theoretical results on the quiet Sun and active region studies, covering the entire radio range from millimeter to decameter wavelengths. We examine small-and large-scale structures, at short and long time scales, as well as synoptic aspects. Open questions and challenges for the future are also identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 108 publications
6
79
0
1
Order By: Relevance
“…At all the NRH frequencies, the corona exhibits a variety of scales, from more than 1 R s (long dark channels, large holes at HF, elongated bright areas at LF) down to the resolution limit (small holes, fine structure in large holes, transverse dimension of dark channels, bright spots in particular near cycle minimum). It was already known from a few observations that the aspect of the corona was not the same at 408 and 169 MHz (Shibasaki et al 2011). We showed that this aspect progressively changes from high to low frequencies, with a loss of contrast (in particular for coronal holes) from 450 down to 230 MHz and that a marked transition occurs below 230 MHz.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…At all the NRH frequencies, the corona exhibits a variety of scales, from more than 1 R s (long dark channels, large holes at HF, elongated bright areas at LF) down to the resolution limit (small holes, fine structure in large holes, transverse dimension of dark channels, bright spots in particular near cycle minimum). It was already known from a few observations that the aspect of the corona was not the same at 408 and 169 MHz (Shibasaki et al 2011). We showed that this aspect progressively changes from high to low frequencies, with a loss of contrast (in particular for coronal holes) from 450 down to 230 MHz and that a marked transition occurs below 230 MHz.…”
Section: Discussionsupporting
confidence: 46%
“…We had already shown that the structure of the CV in the uv plane is complex and has smallscale features (see Fig. 6 in Shibasaki et al 2011) and requires a dense uv coverage to be properly described. It follows that radio imaging is difficult but, when performed simultaneously at several frequencies, is a promising tool for investigating the 3D structure of the corona.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It consists of free-free emission from quiet sun coronal plasma and gyromagnetic emission from sunspots in active regions (e.g. Shibasaki et al 2011, and references therein).…”
Section: Indices From Observations Of the Transition Region And Solarmentioning
confidence: 99%